2017
DOI: 10.1038/modpathol.2016.202
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and gene amplification of PD-L1 in cancer cells and PD-L1+ immune cells in Epstein–Barr virus-associated gastric cancer: the prognostic implications

Abstract: Cancer cells use PD-L1 to evade antitumor immunity through interaction with programmed cell death protein 1 (PD-1) on T cells. Recent whole-genome sequence studies revealed frequent gene amplification of PD-L1 in Epstein-Barr virus-associated gastric cancer (EBVaGC). To investigate the significance of PD-L1 in cancer cells and their microenvironment in EBVaGC, we studied PD-L1 expression by analysis of the public database and immunohistochemistry with fluorescent in situ hybridization (FISH) of the PD-L1 gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 45 publications
9
115
3
Order By: Relevance
“…Further IHC analysis of a large series of 232 GCs from Japan showed that EBVaGC (42% of the series) had higher PD‐L1 expression in tumor cells (34%) and in immune cells from the tumor stroma (45%) than non‐EBVaGC. In EBVaGC, PD‐L1 expression in tumor and immune cells was associated with the diffuse histologic type, tumor invasion depth, and poor patient prognosis . Also corroborating the TCGA results, 11% of EBVaGC had PD‐L1 gene amplification.…”
Section: Molecular Classification Of Gastric Cancersupporting
confidence: 80%
See 1 more Smart Citation
“…Further IHC analysis of a large series of 232 GCs from Japan showed that EBVaGC (42% of the series) had higher PD‐L1 expression in tumor cells (34%) and in immune cells from the tumor stroma (45%) than non‐EBVaGC. In EBVaGC, PD‐L1 expression in tumor and immune cells was associated with the diffuse histologic type, tumor invasion depth, and poor patient prognosis . Also corroborating the TCGA results, 11% of EBVaGC had PD‐L1 gene amplification.…”
Section: Molecular Classification Of Gastric Cancersupporting
confidence: 80%
“…Similarly, Saito et al . analyzed the TCGA database and showed that EBVaGC express higher levels of PD‐L1 mRNA than the other TCGA GC subtypes.…”
Section: Molecular Classification Of Gastric Cancermentioning
confidence: 99%
“…In contrast to our data, an inverse correlation between tumor PD-L1 expression and outcome of HNSCC patients has recently been shown in a Chinese cohort (42), which might be at least partially explained by the lack of distinction of the HPV status and/or a distinct pathogenesis among ethnic groups. This might be of great impact, as high PD-L1 expression levels can be mediated by external stimuli, including cytokines secreted from immune cells, or intrinsic constitutive expression due to gene amplification (43), utilization of an ectopic promoter by translocation (44), disruption of the 3′ untranslated region of PD-L1 (45), or aberrant signaling pathways (46). Based on our previous data in melanoma (32), we investigated the ratios as well as the spatial relationship between CD8 + T cells and immune suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high PD‐L1 levels on retrovirus‐infected cells result in evasion of cytotoxic killing, demonstrating that PD‐L1 expression by target cells can ultimately determine their elimination . Moreover, various cancers can override cytotoxic elimination by a mechanism dependent on tumour PD‐L1 over‐expression, which can be the result of aberrant PD‐L1 gene amplification . Therefore, effective cytotoxic control is not only determined by CD8 T‐cell numbers and their intrinsic function and killing potential, but also by the susceptibility of the target cells themselves, which is greatly influenced by the expression of inhibitory ligands.…”
Section: Treg Cells and Pd‐1 Suppress Immune Responses During Antigenmentioning
confidence: 99%
“…27 Moreover, various cancers can override cytotoxic elimination by a mechanism dependent on tumour PD-L1 over-expression, which can be the result of aberrant PD-L1 gene amplification. [28][29][30][31] Therefore, effective cytotoxic control is not only determined by CD8 T-cell numbers and their intrinsic function and killing potential, but also by the susceptibility of the target cells themselves, which is greatly influenced by the expression of inhibitory ligands.…”
Section: Treg Cells and Pd-1 Suppress Immune Responses During Antigenmentioning
confidence: 99%